Post-School Transitions in Ireland: A case study of Russian speaking students - Faas, Daniel; Darmody, Merike (My University, 2019)
This article examines the post-school pathways of Russian-speaking students in Ireland after completing secondary education; the importance of personal and institutional factors in shaping their transition process, and the role of parents and schools in achieving the post-school goals. The article draws on the qualitative exploratory study of 14 Russian-speaking migrant-origin students, to see how this group progresses beyond secondary schooling in the Irish education system. The study found that all participants had high educational aspirations. Most students achieved their desired first-choice post-school pathway, despite coming from a different linguistic and cultural background. The article points to a range of factors, which affect the post-school transition of migrant young people. The findings are discussed in light of Ireland’s liberal welfare state model with neo-liberal tendencies where those in positions of power can buy into the advantages of the more neo-liberal side of the regime.
PUBLISHED
Keywords: Post-school pathways; Educational transitions; Russian-speaking students; Educational aspirations; Ireland; Identities in Transformation; International Integration